Unusual 'feathery' cause of a parapharyngeal abscess in an infant. (17th January 2018) - Cho, Wai Sum; Nistor, Mihaela; Ubayasiri, Kishan; Johnston, Mark
Abstract : A 7-month-old boy presented to the emergency department with reduced oral intake, neck swelling and fever. Clinical examination revealed a 3 cm left parotid and left level I neck swelling with left medialised tonsil but no trismus. Computed imaging confirmed the presence of an abscess in the peritonsillar area with extension into the parapharyngeal space and deep lobe of the parotid gland. The abscess was incised and drained transorally. Following drainage of the abscess, a small 3 mm suspicious foreign body was seen. After extraction, this was revealed to be a 60 mm feather. We would like to highlight this unusual case in an infant and to ensure that foreign body is considered as aetiology. There are only a handful of cases in the literature involving feathers causing neck abscesses and, to our knowledge, this is the first case where the patient presented with a pharyngeal abscess, which was drained transorally.